2022
DOI: 10.18061/ojph.v5i1.8982
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences, Race, and Health Outcomes: Examining a Synergistic Relationship

Abstract: Background: Adverse childhood experiences (ACEs) are potentially traumatic incidents occurring before age 18 years. Adverse childhood experiences include physical or mental abuse, financial stress, home or community violence, substance misuse, familial turmoil, and other factors. Adverse childhood experiences are associated with negative health outcomes in adulthood. Methods: Numerous research studies and systematic reviews were reviewed to assess the breadth and depth of racial and ethnic inclusivity in ACE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Moreover, Gu et al (2022) suggested that the higher frequency of ACEs among Hispanic and Black youth may lead to potential differences in the types of ACEs experienced and the pathways through which these experiences influence health among different racial and ethnic groups. These findings indicate that the effects of ACEs on various outcomes, including delinquency and mental health, can vary across racial and ethnic lines [ 24 ]. Childhood trauma is marked in a sizable fraction of inmates, with 37% experiencing physical neglect and 68% emotional neglect, with dissociative identity disorder and development of aggressive and violent behaviours being visible.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Gu et al (2022) suggested that the higher frequency of ACEs among Hispanic and Black youth may lead to potential differences in the types of ACEs experienced and the pathways through which these experiences influence health among different racial and ethnic groups. These findings indicate that the effects of ACEs on various outcomes, including delinquency and mental health, can vary across racial and ethnic lines [ 24 ]. Childhood trauma is marked in a sizable fraction of inmates, with 37% experiencing physical neglect and 68% emotional neglect, with dissociative identity disorder and development of aggressive and violent behaviours being visible.…”
Section: Introductionmentioning
confidence: 99%